Learning English through Short Videos: Exploring Students’ Experiences in an EFL Classroom - Diana Dian Sari Tampubolon; Selviana Napitupulu (CV. Doki Course and Training, 2026)
The growing use of short video platforms such as TikTok, YouTube Shorts, and Instagram Reels has increasingly influenced how students are exposed to English. In Indonesian English as a Foreign Language (EFL) classrooms, short videos are often used as supplementary learning media; however, empirical studies that focus on students’ actual learning experiences remain limited. This study aims to explore students’ experiences of learning English through short videos in an Indonesian EFL classroom. A qualitative descriptive research design was employed. The participants were ten eighth-grade students from a private junior high school in Pematangsiantar, Indonesia, selected through purposive sampling. Data were collected through classroom observations and semi-structured interviews and analyzed using thematic analysis. The findings reveal that short videos create a more engaging and less intimidating learning environment, facilitate vocabulary comprehension through visual and contextual support, and increase students’ confidence in classroom interaction. However, students also encountered challenges, particularly related to fast speech and limited processing time. This study contributes to EFL research by providing empirical insights into students’ lived experiences of short video–based learning in the Indonesian EFL context. The findings offer practical implications for EFL teachers, highlighting the importance of careful video selection and pedagogical scaffolding to optimize the use of short videos in classroom instruction